Assessment of Minerals, Bioactive Compounds, and Antioxidant Activity of Ten Moroccan Pomegranate Cultivars - Sarah Loukhmas; Ebrahim Kerak; Meriem Outaki; Majdouline Belaqziz; Hasnaâ Harrak (Journal of Food Quality)
The attractiveness of pomegranate (Punica granatum L.) is increasing worldwide among producers and consumers. Depending on its characteristics, the pomegranate may be intended for fresh consumption, for industrial processing, or for medical purposes. This study aims to assess the variability in terms of mineral content and biochemical properties of ten selected pomegranate cultivars grown in the center of Morocco to better know their fruit potential. Mineral composition, organic acids, total polyphenols, anthocyanins content, individual phenolic compounds, and antioxidant activity were determined in pomegranate juices. Results showed significant differences between cultivars. The sour cultivar “Lhamdha” is rich in organic acids, gallagyl esters, and ellagitannins and showed high antioxidant activity. It could therefore be used as a source for nutraceutical substances. The cultivar “Sefri” of Lalla Takerkoust showed important content of mineral elements, especially iodine (I), calcium (Ca), magnesium (Mg), iron (Fe), and silver (Ag). The cultivars “Sefri” of Ouled Abdellah, “Sefri” of Beni Meskine, “Lahmer,” and “Marrakchia” are suitable for production of fresh pomegranate juice with high potential of health benefits. In fact, they are rich in anthocyanins, polyphenols, and oxalic and ascorbic acids and they presented high antioxidant activity. While the cultivars “Sefri” of Sour Laaz, “Sefri” of Tmassine, “Sefri” of Sidi Abdellah, and “Bzeq Tir” could be intended for fresh fruit consumption. Cluster analysis has revealed the divergence of cultivars with the same appellation “Sefri” confirming the problem of homonymy or synonymy in the pomegranate cultivars appellation. This study clearly demonstrates the nutritional and functional potential of the studied cultivars and the importance of their valorisation, especially for food and pharmaceutical industries.